Shock index and modified shock index as triage screening tools for sepsis - Saqer M. Althunayyan; Yousef M. Alsofayan; Anas A. Khan (Elsevier, 2019)
Background: Fever is one of the common conditions encountered in the emergency department, which related to a spectrum of diseases severity. Identifying sepsis patients from uncomplicated febrile patients is challenging in the emergency triage areas and pre-hospital settings. Objectives: Assess the triage shock index (SI) and modified shock index (MSI) in febrile patients as predictors for sepsis and sepsis-related outcomes. Design: A retrospective cohort study. Setting: Patients presented to the Emergency Department of King Khalid University Hospital. Patients and methods: The analysis included all febrile adult patients triaged with a temperature of 38 °C or more from January 2016 to December 2017. Based on triage vital sign we calculate the SI with cut-off levels of ≥0.7 and ≥1 and MSI with cut-off levels of ≥1 and ≥1.3. We report the Relative Risk, Sensitivity, Specificity, Positive and Negative Predictive Values of the predictors. Main outcome measures: Sepsis and sepsis-related outcomes such as hyperlactatemia, ICU admission, and 28 days mortality. Sample size: 274 patients. Results: 274 patients met our inclusion/exclusion criteria. Of the 274 patients, 252 patient (92%) were septic, 62 patients (22%) had hyperlactatemia, 20 patients admitted to the ICU, and 5 patient died within 28 days. An MSI of ≥1 had a sensitivity of 90% for sepsis predication, 85% for ICU admission and 100% for 28 days mortality. MSI of ≥1.3 showed a specificity (59%-100%) for all the outcomes of interest. Non-significant statistical trends of greater accuracy of MSI over SI. Conclusion: MSI and SI were found to be promising predictors in triaging febrile patients. However no single cut-off values of MSI or SI were found to have an optimal accuracy for prediction of sepsis and sepsis-related outcomes. Further studies are required to assess the incorporation of MSI in a multi-item scaling system for the prediction of sepsis and its related outcomes. Limitations: Small single center study and the results may not be generalizable. Keywords: Sepsis, Fever, Shock index, Modified shock index